On Intuitionistic Fuzzy Quasi Metric Space - Alaa J. Edan; Sameer Q. Hasan (Al-Mustansiriyah Journal of Science, 2022)
In this article the fixed point of intuitionistic fuzzy quasi metric space instabilities on two metrics  dx(f, g) and Dx(f, g) on complicity space X have been studied and presented in details depended on (0,1]-fuzzy contractive map. The illustrative example is proposed to explain the present results using quick sort algorithm.